Molecular Biomarkers of Sessile Serrated Adenoma/Polyps. Issue 12 (December 2019) - Kanth, Priyanka; Boylan, Katherine E.; Bronner, Mary P.; Boucher, Kenneth M.; Hazel, Mark W.; Yao, Ruoxin; Pop, Stelian; Bernard, Philip S.; Delker, Don A.
Abstract : OBJECTIVES: Sessile serrated adenoma/polyps (SSA/Ps) contribute up to 30% of all colon cancers. There is considerable histological overlap between SSA/Ps and hyperplastic polyps. Inadequate consensus exists among pathologists, and no molecular biomarkers exist to differentiate these lesions with high accuracy. Lack of reliable diagnosis adversely affects clinical care. We previously defined a novel 7-gene panel by RNA sequencing that differentiates SSA/Ps from hyperplastic polyps. Here, we use the 7-gene panel as a molecular approach to differentiate SSA/Ps and HPs with higher sensitivity and specificity in a large sample set from a tertiary health care center. METHODS: Reverse transcription quantitative polymerase chain reaction of the 7-gene panel was performed on 223 formalin-fixed, paraffin-embedded serrated polyp and normal colon samples. We compare the sensitivity and specificity of the 7-gene panel with the BRAF and KRAS mutation incidence in differentiating SSA/Ps and HPs. We also evaluate the clinical data of patients with SSA/Ps showing high and low expression of the gene panel. RESULTS: The 7-gene RNA expression panel differentiates SSA/Ps and HPs with 89.2% sensitivity and 88.4% specificity. The gene panel outperforms BRAF mutation in identification of SSA/Ps. Clinical data suggest that expression of the 7-gene panel correlates with the development of SSA/Ps in the future. DISCUSSION: This study describes a novel 7-gene panel that identifies SSA/Ps with improved accuracy. Our data show that RNA markers of SSA/Ps advance the distinction of serrated lesions and contribute to the study of the serrated pathway to colon cancer.